COMPLIMENTS IN THE EDUCATIONAL INSTITUTION: COMPLIMENTS AMONG INDONESIAN STUDENTS OF ENGLISH DEPARTMENT - Nugraha Krisdiyanta (International Journal of Humanity Studies (IJHS), 2019)
This research is conducted to investigate how Indonesian people give compliment to others in English to find the formula of the compliment the students use. The subject of the research is 27 Indonesian students of English Department from three universities. The data are collected by giving questionnaire to the students using the Discourse Completion Task. Students are asked to complete the sentences for giving compliment. The compliments requested are about appearance which consists of hairstyle, dress and figure; and ability and performance which consists of test result, getting the scholar and cooking ability. The result shows that for appearance, the most used formula is by using the word look then the use of be+adj. For ability and performance, students use the word congratulation and be+adj for cooking ability. However, some students give compliment based on Bahasa Indonesia form, not English form by giving some statements which are not related to the context. It is affirmed that compliment is influenced by the language that the people use and it is different from one culture to another.